ANALISIS DETERMINAN FAKTOR PENDAPATAN PARA PEDAGANG DI PASAR REMBIGA KECAMATAN SELAPARANG - ahmad suriadi; Ahmad Suhendri (JURNAL KOMPETITIF : MEDIA INFORMASI EKONOMI PEMBANGUNAN, MANAJEMEN DAN AKUNTANSI, 2018)
This research entitled "Determinant Analysis of Revenue Factor of Merchants in Pasar Rembiga Kecamatan Selaparang Mataram City" This study aims to know the significance of the effect of Capital, Location, and Condition of Trade Place simultaneously, partially, and Dominant to the Revenue of Traders. The type of research used in this study is the method of association (causality). The population of this research is traders in Rembiga market Kecamatan Selaparan Mataram city with a sample of 70 people. The type of data used in this study is Primary data ie data taken directly from the trader by using quesioner. While the data analysis using multiple linear regression analysis. Based on the results of research that has been done, it is concluded from the results of t test analysis found that the variables of Capital, Location and Condition of Selling Place partially significant (meaningful) to Revenue of Merchants in Rembiga Market Selaparang Subdistrict Mataram City. From the results of F test analysis found that the variables of Capital, Location and Condition of Selling Place Simultaneously / Together have significant (meaningful) to the Revenue of Merchants in Pasar Rembiga Kecamatan Selaparang Mataram City. Capital Variable has a dominant influence on Revenue of Merchants in Pasar Rembiga Kecamatan Selaparang Mataram City